Prevalence of Hepatitis B, C, and D among Thalassemia patients in Sulaimani Governorate - Hama, Salih Ahmed; Sawa, Moaid Ibrahim (Kurdistan Journal of Applied Research, 2017)
Infectious diseases are the leading cause of mortality worldwide, with hepatitis viruses in particular making global impact on socioeconomic development and this infection remains a serious public health issue. This study was performed to investigate the prevalence of Hepatitis B, C and D among multi-transfused risk groups in Sulaimani Governorate, 120 major thalassemic patients were tested by serological and enzyme-linked immunosorbent assay (ELISA) technique and Recombinant ImmunoBlot Assay (RIBA) test was done as a confirmatory test for all HCV ELISA positive patients. It was observed that the prevalence of HCV was higher (29.1%) comparing to HBV (22.5%) and HDV (3.3%). The prevalence of HCV-HBV coinfection was (5%), HCV-HBV-HDV coinfections were (0.83%). Statistical analysis showed that the age was significantly effective on the prevalence of HBV (p = 0.009), parenteral medication users showed a significant relation with HBV and HCV prevalence (p = 0.03 and 0.041) respectively. The blood transfusion frequency was significantly related to HBV and HCV prevalence (p = 0.042 and 0.035) respectively. It was noticed that vaccination significantly related to HBV prevalence among thalassemic patients (p = 0.002).